PENGARUH NET WORKING CAPITAL TERHADAP MARGIN SOLVENCY PADA PT. ASURANSI JASA INDONESIA (PERSERO) CABANG KORPORASI BANDUNG - Lutfhid Sevriana, - (2010)
Actually, Insurance companies needs to maintain their existence by doing cooperation with another party, especially their customer. A Considering factor for the customer for their loyalty to their insurance company is to know insurance health financial condition. One of many ways to know insurance health financial condition is by counting its margin solvency. High value of margin solvency can be achieved by a proper net working capital management. But at PT. Asuransi Jasa Indonesia (Persero) corporation branch Bandung from 1999 to 2008 periods there is fluctuation value that leaned into unreachable margin solvency standard. Because of that, this research have purposes to know net working capital condition, margin solvency condition, and the influence of net working capital to margin solvency at PT. Asuransi Jasa Indonesia (Persero) corporation branch Bandung (Jasindo korporasi Bandung). This thesis is using causal research design that is observation design which used to know the influence between one variable with another variable. The data source in this thesis is Financial Statement Jasindo korporasi Bandung start from 1999 to 2008. The data processing of net working capital is using qualitative working capital's concept while the data processing of margin solvency is using early warning system ratio's tool. Based on the result of this research, the writer concluded that net working capital's condition is classified as fluctuated and continue experience up and down. Average value of net working capital at Jasindo korporasi Bandung start from 31th December 1999 to 31thDecember 2008 is Rp.244,838,482,000.-. While margin solvency of Jasindo korporasi Bandung that leaned into being down from one period to the next period. Average value of margin solvency is stated as "not good" because it still well of under margin solvency's average standard in sets of early warning system ratio that equal to 33.33%. The influence of net working capital to margin solvency at Jasindo korporasi Bandung is positive with regression coefficient's result equal to 0.71. The meaning is when net working capital arise, margin solvency also arise and so does the opposite, when net working capital decline, margin solvency also decline. Keywords: Net Working Capital, Margin Solvency